Eso Astrophysics Symposia
DOI: 10.1007/10849171_69
|View full text |Cite
|
Sign up to set email alerts
|

Terapixel Surveys for Cosmic Shear

Abstract: Abstract. The recent detections of cosmic shear signal announced by several groups have demonstrated the feasibility of this challenging program and convinced astronomers of its potential for cosmology. Cosmic shear analysis demands to handle Gigabytes of data in order to probe several square degrees in subarcsecond deep imaging mode. The success of these surveys is sensitive to the designs of the observation strategy, the organization of the data reduction pipelines and the links of the data base with surveys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…They will therefore be improved upon by ongoing surveys on existing telescopes, such as the Legacy Survey on CFHT (CFHTLS; Mellier et al 2000), the Deep Lens Survey , surveys with the Subaru telescope (Hiroyasu et al 2001) and the Sloan Digital Sky Survey (Stebbins, McKay & Frieman 1995). Future instruments dedicated to surveys and for which cosmic shear is a primary science driver are being planned, such as Megacam on CFHT (Boulade et al 2000), the Visible and Infrared Survey Telescope for Astronomy (VISTA; Taylor et al 2003), the Large aperture Synoptic Survey Telescope (LSST; Tyson et al 2002a,b), or the novel Panoramic Survey Telescope and Rapid Response System (Pan-STARRS; Kaiser, Tonry & Luppino 2000).…”
Section: Future Surveys and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…They will therefore be improved upon by ongoing surveys on existing telescopes, such as the Legacy Survey on CFHT (CFHTLS; Mellier et al 2000), the Deep Lens Survey , surveys with the Subaru telescope (Hiroyasu et al 2001) and the Sloan Digital Sky Survey (Stebbins, McKay & Frieman 1995). Future instruments dedicated to surveys and for which cosmic shear is a primary science driver are being planned, such as Megacam on CFHT (Boulade et al 2000), the Visible and Infrared Survey Telescope for Astronomy (VISTA; Taylor et al 2003), the Large aperture Synoptic Survey Telescope (LSST; Tyson et al 2002a,b), or the novel Panoramic Survey Telescope and Rapid Response System (Pan-STARRS; Kaiser, Tonry & Luppino 2000).…”
Section: Future Surveys and Prospectsmentioning
confidence: 99%
“…It relies on the measurement of the distortions that lensing induces in the images of background galaxies (for reviews, see Bartelmann & Schneider 1999, Bernardeau 1999, Kaiser 1999, Mellier 1999, Narayan & Bartelmann 1996, Schneider 1995). This method is now widely used to map the mass of clusters of galaxies (see Fort & Mellier 1994 for a review) and has been extended to the study of superclusters (Gray et al 2002, Kaiser et al 1998) and groups . Recently, weak lensing was statistically detected for the first time in random patches of the sky (Brown et al 2003;Bacon et al 2002;Bacon, Refregier & Ellis 2000;Hamana et al 2003;Hämmerle et al 2002;Jarvis et al 2002;Kaiser, Wilson & Luppino 2000;Maoli et al 2001;Refregier, Rhodes, & Groth 2002;Rhodes, Refregier & Groth 2001;van Waerbeke et al 2001a;van Waerbeke et al 2002;Wittman et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We can turn around the argument and use this technique to blindly search for new, hitherto unknown mass concentrations. So far, 9 candidates for such mass concentrations detected by weak lensing techniques have been reported in the literature (Erben et al 2000;Umetsu & Futamase 2000;Mellier et al 2000;Wittman et al 2001;Miralles et al 2002;Wittman et al 2002;Dahle et al 2003). Five of them (Wittman et al 2001(Wittman et al , 2002Mellier et al 2000, and two of the three candidates in Dahle et al 2003) have been confirmed as galaxy clusters.…”
Section: Introductionmentioning
confidence: 98%
“…So far, 9 candidates for such mass concentrations detected by weak lensing techniques have been reported in the literature (Erben et al 2000;Umetsu & Futamase 2000;Mellier et al 2000;Wittman et al 2001;Miralles et al 2002;Wittman et al 2002;Dahle et al 2003). Five of them (Wittman et al 2001(Wittman et al , 2002Mellier et al 2000, and two of the three candidates in Dahle et al 2003) have been confirmed as galaxy clusters. The other four candidates lack optical counterparts and are thus potentially dark clusters with an unusually high M/L ratio.…”
Section: Introductionmentioning
confidence: 98%
“…Many larger and more ambitious surveys are ongoing, planned, or proposed. These include the Deep Lens Survey [22]; the National Optical Astronomy Observatory (NOAO) Deep Survey; the Canada-France-Hawaii telescope (CFHT) Legacy Survey [23]; Pan-STARRS; supernova acceleration probe (SNAP) [24 -26]; and large synoptic survey telescope (LSST) [27]. A major challenge for the future of WL studies is to have a very tight control of systematic errors.…”
Section: Introductionmentioning
confidence: 99%